Electricity distribution grids resilience enhancement by network reconfiguration. (28th July 2021) - Sabouhi, Hamed; Doroudi, Aref; Fotuhi‐Firuzabad, Mahmud; Bashiri, Mahdi
Summary: Electric power systems try to maximize resilience by various enhancement strategies as preventive and corrective actions against extreme weather events. This paper presents an operational network reconfiguration strategy during a high wind event to strengthen the resiliency of distribution networks. In the proposed resilience enhancement strategy, a bi‐level optimization problem is formulated with two conflicting objectives (i) maximizing grid resilience and (ii) realize the primary objective by a minimum number of out‐of‐service lines (OSLs) switching operations. Furthermore, the algorithm considers the priority of loads, which is an important characteristic of modern distribution grids. The optimization problem is solved by the bi‐level genetic algorithm (BiGA). The IEEE 33‐bus network is utilized to demonstrate the application of the developed algorithm. The simulation results show a significant improvement in the resiliency of the tested network and reveal that switching operations can be used effectively to increase the resiliency of distribution networks against natural disasters. Furthermore, sensitivity analysis is performed to show the effectiveness of the proposed approach for finding the global optimal point. The proposed network reconfiguration strategy helps to prepare for severe weather conditions. Abstract : This paper presents a novel operational network reconfiguration strategy by topology switching during a high wind event to strengthen the resiliency of distribution networks. In the proposed resilience enhancement strategy, a bi‐level optimization problem is formulated with two conflict objectives (i) maximizing grid resilience and (ii) realize the leader objective within the minimum number of out‐of‐service lines switching operations.